Leopold and Loeb teen killers - Koopmans, Andy (Thomson Dale, 2004)
Discusses the notorious trial of teenagers Nathan Leopold Jr. and Richard Loeb, who, on May 21, 1924, abducted and murdered a fourteen-year-old boy. Includes discussion of the backgounds of the two young murderers and their victim, the psychological ramifications of the crime, and famed civil rights attorney Clarence Darrow's defense strategy.